A review of the ecology, colonization and genetic characterization of Salmonella enterica serovar Sofia, a prolific but avirulent poultry serovar in Australia - Duffy, L.; Dykes, Gary; Fegan, N. (2012)
The distribution of Salmonella serovars on Australian poultry is dominated by the presence of Salmonella enterica subspecies II 1,4,12,27:b:[e,n,x](S. Sofia). The predominance on poultry (40–60%) and a very low level of disease in humans in Australia (0.3%) is unique compared to the rest of the world. This review aims to consolidate the published information on S. Sofia and suggests factors which may be relevant as to why this unique situation exists in Australia. An increase in percentage survival of this serovar relative to other Salmonella serovars through poultry processing, suggests a possible survival mechanism against poultry processing stresses. Factors related to survival including those involved in attachment to surfaces, have been investigated in different strains of S. Sofia. The ability of S. Sofia to adhere to abiotic surfaces was strain dependent and production of cellulose was found to be a poor indicator of attachment potential. Genetic characterization studies of S. Sofia in comparison to Salmonella Typhimurium noted major differences between the Salmonella pathogenicity islands 1, 3 and 5. It is unclear which, if any of these play a role in the dominance of S. Sofia within Australian poultry or the lack of disease causing strains in humans. Further investigation into the mechanism of colonization of chickens, survival through processing, and avirulence for humans may lead to a greater understanding of factors impacting on the ecology of Salmonella in poultry. These may in turn assist in the development of controls and management systems for the more virulent Salmonella serovars.